2014
DOI: 10.3892/ijo.2014.2551
|View full text |Cite
|
Sign up to set email alerts
|

ISO-66, a novel inhibitor of macrophage migration inhibitory factor, shows efficacy in melanoma and colon cancer models

Abstract: Macrophage migration inhibitory factor (MIF) is a pleiotropic pro-inflammatory cytokine, which possesses a contributing role in cancer progression and metastasis and, thus, is now considered a promising anticancer drug target. Many MIF-inactivating strategies have proven successful in delaying cancer growth. Here, we report on the synthesis of ISO-66, a novel, highly stable, small-molecule MIF inhibitor, an analog of ISO-1 with improved characteristics. The MIF:ISO-66 co-crystal structure demonstrated that ISO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
(72 reference statements)
0
24
0
Order By: Relevance
“…More recently, the ability of this cytokine to support tumor progression has been highlighted, revealing MIF as a potential target for anticancer therapies in melanoma and colon cancer (40). MIF occurs in immunologically distinct conformational isoforms, reduced MIF and oxidized MIF (oxMIF), with the latter predominantly expressed in patients with inflammatory diseases (41) and is highly expressed by various cancer cell lines (42).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the ability of this cytokine to support tumor progression has been highlighted, revealing MIF as a potential target for anticancer therapies in melanoma and colon cancer (40). MIF occurs in immunologically distinct conformational isoforms, reduced MIF and oxidized MIF (oxMIF), with the latter predominantly expressed in patients with inflammatory diseases (41) and is highly expressed by various cancer cell lines (42).…”
Section: Discussionmentioning
confidence: 99%
“…ISO-1 exerts an inhibitory action on cell migration and invasion in vitro in adenoid cystic carcinoma, as demonstrated by a decrease in MMP-9 expression (46). Additionally, an analog of ISO-1, ISO-66, has recently been reported to be active in melanoma and colon cancer models, where it decreases tumor growth by stimulating an antitumor immune response in vivo (56). Regarding head and neck carcinoma, our previous study investigated the effect of 4-IPP on SCCVII cells and reported that the pharmacological inhibition of MIF resulted in impaired proliferation and invasiveness in vitro (43).…”
Section: Mif and Angiogenesismentioning
confidence: 99%
“…Anti-MIF therapeutics are therefore believed to have considerable promise for many types of cancer [5357], Indeed several MIF-inactivating strategies have proven successful in delaying cancer growth, including ISO-66, a synthetic MIF inhibitor which caused a significant decrease in tumor burden when administered to mice with established syngeneic melanoma or colon cancer [58]. Recently human anti-MIF antibodies have been tested for their ability to influence growth rate and invasion of the human PC3 prostate cancer cell line in vitro , and in a PC3-xenograft mouse model in vivo .…”
Section: Therapeutic Targetsmentioning
confidence: 99%